Predicting and coding sound into action translation in spinal cord injured people - Grisoni, Luigi; Piperno, Giulio; Moreau, Quentin; Molinari, Marco; Scivoletto, Giorgio; Aglioti, Salvatore Maria (The European journal of neuroscience, 2024)
Motor activation in response to perception of action‐related stimuli may depend on a resonance mechanism subserving action understanding. The extent to which this mechanism is innate or learned from sensorimotor experience is still unclear. Here, we recorded EEG while people with paraplegia or tetraplegia consequent to spinal cord injury (SCI) and healthy control participants were presented with action sounds produced by body parts (mouth, hands or feet) that were or were not affected by SCI. Non‐action sounds were used as further control. We observed reduced brain activation in subjects affected by SCI at both pre‐ and post‐stimulus latencies specifically for those actions whose effector was disconnected by the spinal lesion (i.e., hand sound for tetraplegia and leg sound for both paraplegia and tetraplegia). Correlation analyses showed that these modulations were functionally linked with the chronicity of the lesion, indicating that the longer the time the lesion‐ EEG data acquisition interval and/or the more the lesion occurred at a young age, the weaker was the cortical activity in response to these action sounds. Tellingly, source estimations confirmed that these modulations originated from a deficit in the motor resonance mechanism, by showing diminished activity in premotor (during prediction and perception) and near the primary motor (during perception) areas. Such dissociation along the cortical hierarchy is consistent with both previous reports in healthy subjects and with hierarchical predictive coding accounts. Overall, these data expand on the notion that sensorimotor experience maintains the cortical representations relevant to anticipate and perceive action‐related stimuli. We run a mismatch‐negativity based EEG study on people with acquired paraplegia or tetraplegia and healthy controls, to look for possible alteration on prediction and perception processes of action‐related sounds following a spinal lesion. We found reduced motor resonance for action sound stimuli related to the effectors disconnected by the lesion. Source estimations further suggested that the patients decrease in activity within the motor areas was a contributing factor to these alterations.